Stock market dynamics and the relative importance of domestic, foreign, and common shocks - Martin Ademmer; Wolfram Horn; Josefine Quast (International Journal of Finance & Economics, 2020)
We quantify the contemporaneous relationships among stock markets in the euro area, the United States, and a group of emerging economies over the period from 2008 to 2017. Exploiting the heteroskedasticity in the stock market data, we identify shocks that originated in the respective domestic markets and shocks that are common to all markets. Our results underline the leading role of the United States in international equity markets, but also point to the importance of indirect spillovers for all economies. Variance decompositions show that while domestic shocks explain the bigger part of the variation in each stock market, a substantial part of the variation in the euro area and the emerging economies can be attributed to foreign shocks. A comparison with a sample covering the pre-crisis period from 1999 to 2007 suggests a strengthening of the linkages among global stock markets in recent years. In particular, the spillovers from advanced to emerging economies have become more pronounced.
Keywords: 330; financial linkages; heteroskedasticity; identification; spillovers; stock markets